Unravelling adherence to prophylaxis in haemophilia: a patients' perspective. (9th April 2015) - Schrijvers, L. H.; Kars, M. C.; Beijlevelt‐van der Zande, M.; Peters, M.; Schuurmans, M. J.; Fischer, K.
Summary Given the lifelong therapy in haemophilia patients, insight in non‐adherence behaviour from a patient perspective is important to understand patients' difficulties with the following treatment recommendations. The aim of this study was to clarify the process underlying adherence (behaviour) to prophylactic treatment, from a patients' perspective. To develop a grounded theory, a qualitative study using individual in‐depth interviews was performed to understand experiences, perceptions and beliefs concerning adherence to prophylaxis. From two Dutch treatment centres, 21 adults with haemophilia using prophylaxis were interviewed. Patients were asked how they experience their task to administer prophylaxis and how they adhere to this. The interviews were transcribed, coded and analysed in an iterative process, leading to the development of the grounded theory. Adherence was determined by the position of prophylaxis in life. The position of prophylaxis was determined by the perception of prophylaxis and the ability to exert prophylaxis. Patients' perception was influenced by two main factors: acceptance of haemophilia and feeling/fearing symptoms. The ability to exert prophylaxis was influenced by understanding haemophilia and prophylaxis and planning/infusion skills. The combination of different perceptions and skills led to four main positions of prophylaxis in life: (i) prophylaxis integrated in life, (ii) prophylaxis according to doctors' advice, struggling with irregular situations, (iii) prophylaxis is too much to handle, (iv) prophylaxis is a confrontation with illness. The adherence level gradually decreased from position 1 to 4. This information can be used to design tailored interventions to promote adherence.